USE OF MULTILOOP EDGEWISE ARCHWIRE (MEAW) FOR TREATMENT OF ADULT PATIENTS WITH UNILATERAL POSTERIOR CROSSBITE - Endah Fatonah; Zenith Paskalin; Endah Mardiati; Ida Ayu Evangelina; Avi Laviana (Dentino: Jurnal Kedokteran Gigi, 2025)
Background: The Multiloop Edgewise Archwire (MEAW) technique is a biomechanically efficient orthodontic method employed to correct various malocclusions, including posterior crossbite caused by inadequate transverse relationships between the maxillary and mandibular arches. MEAW archwire incorporate boot loops, providing enhanced flexibility and precise control of tooth movement. Case Report: A 21-year-old female came to the orthodontic clinic with severe maxillary and mandibular crowding, The patient presented with dentoskeletal Class I malocclusion characterized by a convex profile, clockwise rotation of the mandibular plane, retrognathic mandible, ectopic upper canines, anterior and posterior crossbite. The maxillary midline had shifted 2 mm to the right, and the mandibular midline had shifted 4 mm to the right. SNA: 80º, SNB: 76º, and Wit’s appraisal: 2.5 mm. as well as ectopic upper canines. Extraction of the upper and lower first premolars were performed. The combination of MBT 0.022” prescription and MEAW were used for this treatment. Active lacebacks were used to align ectopically erupted upper canines. MEAW was used to correct the posterior crossbite, resulting in improved interdigitation and ideal smile arch. Final Results: Post-treatment cephalometric analysis showed SNA: 80º, SNB: 77º, and Wit’s appraisal: 2.5 mm. Retention was maintained using removable Hawley retainers. Conclusion: MEAW arches are made of 0.016” × 0.022” steel wire, providing flexibility to the archwire and allowing for horizontal and vertical control of tooth positions. Precise construction of MEAW is essential to achieving optimal treatment outcomes and maintaining stable relationships. Keywords: MEAW, multiloop edgewise archwire, posterior crossbite